DEVELOPING NEW TECHNIQUES FOR DIAGNOSING INFECTIOUS DISEASES - Mansour Nasser Almansour, Yazeed Abdullah Alfalah, Amal Mashaan jehad Alshammari (Chelonian Research Foundation, 2022)
Infectious diseases continue to pose a significant threat to public health worldwide, with emerging pathogens and antibiotic resistance contributing to the complexity of diagnosing and treating these conditions. Developing new techniques for diagnosing infectious diseases is crucial in order to improve patient outcomes, prevent the spread of infections, and optimize treatment strategies. This essay explores the importance of developing new diagnostic techniques for infectious diseases at the Master level, highlighting the methodologies, results, and implications of such advancements. By leveraging innovative technologies and strategies, healthcare professionals can better identify and manage infectious diseases, ultimately leading to a healthier global population.